15-4t=13

Simple and best practice solution for 15-4t=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-4t=13 equation:


Simplifying
15 + -4t = 13

Solving
15 + -4t = 13

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -4t = 13 + -15

Combine like terms: 15 + -15 = 0
0 + -4t = 13 + -15
-4t = 13 + -15

Combine like terms: 13 + -15 = -2
-4t = -2

Divide each side by '-4'.
t = 0.5

Simplifying
t = 0.5

See similar equations:

| X=6.13 | | 66+33z= | | -12+P=-13 | | 11x-(2x-9)=72 | | 2v-11=27 | | x=180-102-48 | | t+29=1 | | 54=4w-14 | | (x-7)*3=-9 | | 17x-11=-13x+22 | | z+59=64 | | g=acb | | 2[x-3]=[x-1]+7 | | 6+9(b+4)=114 | | -29-6y+14=-20y+24+11y | | 90y+45= | | z-71=22 | | 10=(i)100 | | B-18=-35 | | 8+20t= | | y=-3-7x | | 2h-4=16 | | 2x^2-4=6x | | 20-10s= | | 7y+3y=20 | | s=69.3-4 | | (18h+19)=(5h) | | 5-1/2(x)=12 | | lx+3l+6=12 | | 5(x-7)+33=4x-2 | | 6-9v=69 | | x^2+4ab=2ax+2bx |

Equations solver categories